2023
DOI: 10.3390/cells12091337
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterisation of the Circular RNA, circHTT(2-6), in Huntington’s Disease

Abstract: Trinucleotide repeat disorders comprise ~20 severe, inherited, human neuromuscular and neurodegenerative disorders, which result from an abnormal expansion of repetitive sequences in the DNA. The most common of these, Huntington’s disease (HD), results from expansion of the CAG repeat region in exon 1 of the HTT gene via an unknown mechanism. Since non-coding RNAs have been implicated in the initiation and progression of many diseases, herein we focused on a circular RNA (circRNA) molecule arising from non-can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Another study found that circHTT 2–6 derived from the exons 2, 3, 4, 5, and 6 of the HTT gene was enriched in in the frontal cortex of HD patients 92 . When circHTT (2–6) was overexpressed in HEK293 and SH‐SY5Y cells, no change in the CAG repeat region of HD was detected, which decreased the cell proliferation, nuclear area, and altered subcellular localization of the HTT protein 92 . These results demonstrate the overexpression of circHTT undergoes HD‐related pathological changes, but its specific functional mechanism needs further study.…”
Section: Circrnas Involved In Regulation Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…Another study found that circHTT 2–6 derived from the exons 2, 3, 4, 5, and 6 of the HTT gene was enriched in in the frontal cortex of HD patients 92 . When circHTT (2–6) was overexpressed in HEK293 and SH‐SY5Y cells, no change in the CAG repeat region of HD was detected, which decreased the cell proliferation, nuclear area, and altered subcellular localization of the HTT protein 92 . These results demonstrate the overexpression of circHTT undergoes HD‐related pathological changes, but its specific functional mechanism needs further study.…”
Section: Circrnas Involved In Regulation Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…To assess the CircRNA mini vector, hereafter called mc, six circRNAs were restriction enzyme-cloned into this vector -EcoRV/SacII cloning sites: circEGFR (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), circEGFR (2)(3)(4)(5)(6), circEGFR (19)(20), circTNIK (5)(6)(7); HpaI/AgeI cloning sites: circNFASC (29)(30), and using the AgeI site only: circBCR(9-14) (Figures 1A-B). All plasmid sequences were confirmed by Sanger sequencing.…”
Section: Circrna Mini Vector Incorporates Molecular Scars Into the Ci...mentioning
confidence: 99%
“…To more thoroughly investigate the fidelity of the circRNA bsj sequence produced from mc2 in cells transfected with this plasmid, a next generation sequencing strategy was devised for each individual circRNA, called circRNA bsj-seq. This was performed on five different circRNAs, including circBCR (9)(10)(11)(12)(13)(14) cloned into both mc2 and the original mc vector in addition to another four circRNAs: circEGFR (19,20), circEGFR (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), circMLL (9) and circMLLT2 (3,4). Using a 12-mer unique molecular identifier, at least 185,000 individual circRNAs were sequenced from HEK293 cells transfected with each different mc/mc2 construct.…”
Section: Mc2 a Universal Vector For Circrna Expression With Scarless ...mentioning
confidence: 99%
See 2 more Smart Citations